Peculiarity of sapphire application in medicine - Lytvynov, L.A. (Functional Materials, 2014)
Considered are the properties of sapphire which make it expedient for application in relatively new branches of medicine such as microsurgery, implantology, medical instrument making. Peculiarities of the use of sapphire and its advantages over the analogues are shown.